Use hierarchy for "liberating servant leadership" instead of controlling employees - Bill Nobles (Journal of Organization Design, 2019)
Since the Industrial Revolution, management has relied on hierarchy to control assets and employees. The negative impact of that hierarchical control on employee performance has long been recognized, yet in spite of expert and scholarly attempts to solve these problems hierarchical control generally continues to dominate management theory and practices. This article argues that is because these problems are rooted not in hierarchy, but rather in organizational expectations of hierarchy. Hierarchy emphasizing "liberating servant leadership" (Dr. Isaac Getz of the ESCP Business School in Paris introduced the term "liberating leadership," the French equivalent of which "entreprise libérée" has become a household term in France. Max De Pree suggested the leader must become a servant in Leadership is an Art. This combines the two concepts.) instead of controlling employees can produce extraordinary business results. Eighteen innovative CEOs (The innovative CEOs and their successful companies in alphabetical order are Bill Gore, W.L. Gore Company; Bob Beyster, Science Applications International Corporation; Bob Davids, Radica Games & Sea Smoke Vineyard and Winery; Bob Koski, Sun Hydraulics; Bob Townsend, AVIS; David Kelley, IDEO; Garry Ridge, WD-40; Gordon Forward, Chaparral Steel; Harry Quadracci, Quad/Graphics; Herb Kelleher, Southwest Airlines; Jeff Westphal, Vertex; Ken Iverson, Nucor Steel; Kim Jordan, New Belgium Brewing; Max De Pree, Herman Miller; Paul Staley, PQ Corporation; Rich Teerlink, Harley Davidson; Robert McDermott, USAA Insurance; and Stan Richards, The Richards Group. Additional details about each leader can be found in the books Freedom, Inc. by Brian Carney and Isaac Getz and Questioning Corporate Hierarchy by Paul Staley and Bill Nobles.) whom I have studied discovered this by trial and error while trying to take advantage of Douglas McGregor's Theory Y. Their leadership changed the design of their organizations. Believing that individuals can drive themselves more effectively than managers can, these CEOs sought to create conditions in which associates committed themselves to organizational objectives, and satisfied their ego and self-development needs. The CEOs relied on hierarchy to control financial assets, but fundamentally changed the human dimension. The organizational roles traditionally called "middle managers" responsible for controlling employees became "liberating servant leaders" responsible for ensuring that associates had everything needed to freely self-control and self-coordinate their efforts. The resulting self-motivated, creative employees played key roles in each CEO's company being extraordinarily successful. These experiences provide a foundation for transforming the human role of hierarchy in organizational design.
Keywords: 650; Empowerment; Freedom; Hierarchy; Culture; Liberating servant leadership